(untitled) (Nordic Journal of Practical Theology, 2020)
The article provides an image of the beginning, growth, and current situation of healthcare chaplaincy in Finland. The history of the chaplaincy takes us back decades, yet the healthcare chaplaincy as we know it today was formed in the 1960s. The Evangelical-Lutheran Church of Finland has played a significant role in the development of the chaplaincy. Two contexts exist as chaplaincy locales: Healthcare and the Evangelical-Lutheran Church of Finland. It took decades for healthcare chaplaincy to find its place within and between these two contexts, yet the recent cutbacks in personnel do not promise easy years for the future. Research within this manifold subject is diverse, but new studies are still needed to tackle the challenges of the changing context, work climate, and divergent needs of the patients.